SIMULATION MODELING OF INVESTMENT EFFICIENCY IN THE INNOVATIVE ACTIVITY OF THE ENTERPRISE - TRUSH, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In this article we will consider the main problems we face in determining the effectiveness of attracting investment in innovation activities of the enterprise. Many researchers have long been developing better mechanisms for evaluating the effectiveness of investment activities. These include simulation techniques and a multi-step approach. As part of this study, we adapt these techniques for the process of evaluating the economic efficiency of innovation, taking into account the identified features. The methods of evaluating the effectiveness of innovation activity in relation to the investment aspect are proposed, the peculiarity of which is the fact that the amount of project money flows and the amount of investment costs, in particular working capital, needed for introducing the assets of an innovative project into for the production with the use of the newest technologies and innovations are taken into consideration. It is proved that the evaluation of the efficiency of investments in the innovation project predetermines processing of expert assessments applying special tools, which involves checking the conditions of consistency and consensus of experts’ ideas. The final stage of the expertise involves making a decision on selection of one or several innovation projects for implementation in the conditions of the enterprise under consideration. It is established that the basis of selection should be the rating of the innovation project, the cost of its implementation and the budget of the enterprise’s innovation development. The final decision on the appropriateness of introduction of the innovation project does not require rigid formalization, but should be taken by senior management board of the enterprise as a result of qualitative assessment of the efficiency of investment in innovation projects. Simulation modeling is proposed, which will allow to make a decision on the effectiveness of attracting investment in an innovative project.